ASEAN HUMAN RIGHTS CHALLENGES: TOWARDS A REGIONAL-BASED SOUTHEAST ASIAN COURT OF HUMAN RIGHTS - I Gede Bagus Ananda Pratama; I Made Budi Arsika (Kertha Negara : Journal Ilmu Hukum, 2014)
As the declaration of ASEAN Human Rights Declaration, ASEAN had enablednew options in its framework of human rights settlement issues in its region. Suchmomentum shall be considered as an entry point in transforming long-standing values ofconsultative and consensual of ASEAN in dealing with human rights issues in ASEAN.Such aforementioned values had been assessed their relevance in handling ASEANhuman rights violations which had been unresolved. The application of regional-basedinstitution by several other regions might be considered as a blueprint for ASEAN courtof human rights in the future.